Karakterisasi Cendawan Rhizosfer pada Tegakan Mahoni di Hutan Pendidikan Universitas Hasanuddin - G Gusmiaty; Siti Halimah Larekeng (Fapetrik-UMPAR, 2020)
Soil fungi, which produce hormones that occupy the rhizosphere ecosystem, have roles as agents to promote plant growth. This study aims to isolate rhizosphere fungi in mahogany in the Experiment Forest of Universitas Hasanuddin, and identify the fungal isolates obtained based on morphological characters. The research began with rhizosphere soil sampling, isolation, and identification based on morphological characters. The rhizosphere microbial isolation on mahogany stands in the Unhas Educational Forest obtained 18 fungal isolates with varied morphological characteristics, both in colony color and elevation. Microscopic observations resulted in 4 genera, namely Rhizopus, Gliocladium, Trichoderma, and Aspergillus. The results showed that there were superior fungi isolates that could produce growth hormones and could be applied to forest plant seeds. The formula with these select fungi can give the seeds optimal growth in forest plant seeds.